Hepatic DNA Damage Induced by Electronic Cigarette Exposure Is Associated With the Modulation of NAD+/PARP1/SIRT1 Axis - Espinoza-Derout, Jorge; Shao, Xuesi M.; Bankole, Emmanuel; Hasan, Kamrul M.; Mtume, Norma; Liu, Yanjun; Sinha-Hikim, Amiya P.; Friedman, Theodore C. (Frontiers in Endocrinology, 2019)
The prevalence of electronic cigarette (e-cigarettes) use has rapidly increased in the world. Use of tobacco products has been associated with DNA damage and metabolic syndrome. Using Apolipoprotein E knockout (ApoE-/-) mice on a western diet (WD), a mouse model of nonalcoholic fatty liver disease (NAFLD), we recently demonstrated that nicotine in e-cigarettes activates hepatocyte apoptosis, and causes hepatic steatosis. This study examines the harmful effects of e-cigarettes on the liver with a special emphasis on DNA damage and mitochondrial dysfunction. ApoE-/- mice were exposed to saline, e-cigarettes without nicotine or e-cigarettes with 2.4% nicotine for 12 weeks using our newly developed mouse e-cigarette exposure model system that delivers nicotine to mice leading to equivalent serum cotinine levels found in human cigarette users. Mice exposed to e-cigarette (2.4%) had increased apurinic/apyrimidinic (AP) sites, a manifestation of DNA damage. Additionally, e-cigarette (2.4%) produced a decrease in NAD+/NADH ratio in hepatic cells, in comparison with saline and e-cigarette (0%). Western blot analysis showed that mice treated with e-cigarette (2.4%) had increased poly (ADP ribose) polymerase (PARP1) activity associated with reduced levels of Sirtuin 1 (SIRT1). Furthermore, hepatic oxidative stress and mitochondrial DNA mutations, as well as hepatic PTEN-induced kinase 1 (PINK1) were increased in mice treated with e-cigarette (2.4%). Transmission electron microscopy revealed that hepatocytes of mice treated with e-cigarette (2.4%) exhibited increased vacuolization of the mitochondria and a reduction in cellular organelles. These results demonstrate the adverse effects of e-cigarettes exposure leading to NAD+ deficiency which may suggest a mechanistic link between e-cigarette-induced hepatic DNA damage and mitochondrial dysfunction.